Recommendations for the treatment of localized prostate cancer by permanent interstitial brachytherapy - Hakenberg, Oliver; Wirth, Manfred; Hermann, T.; Alken, Peter; Kovacs, Gyula; Müller, Rolf-Peter; Ahlemann, L. M.; Schalkhäuser, Klaus (Urologia internationalis, 2003)
The increasing use of interstitial brachytherapy for the treatment of prostate cancer has made it necessary to discuss and establish guidelines for the application of this treatment modality. A group of experts representing the four professional and scientific societies of urologic surgeons and radiation oncologists in Germany was formed by the German Society of Urology (Deutsche Gesellschaft für Urologie, DGU), the Association of German Urologists (Berufsverband der Deutschen Urologen e.V., BDU), the German Society for Radiation Oncology (Deutsche Gesellschaft für Radioonkologie, DEGRO) and the Association of German Radiotherapists (Berufsverband der Deutschen Strahlentherapeuten, BVDSt). This group has formulated a consensus statement consisting of recommendations and guidelines for the indications, planning, implementation and follow-up of permanent interstitial brachytherapy by seed implantation for the treatment of localized prostate cancer. These recommendations also define the responsibilities of the two medical disciplines involved in the use of this interdisciplinary treatment.